1. ## trig-substitution!

i have this $\intk\sqrt{\frac{1-z}{z}}dz$

i set $z=sin^2\theta$
differentiating z w.r.t $\theta$, i have $dz=2sin\theta cos\theta d\theta$
substituting

$2k\int\sqrt{\frac{1-sin^2\theta}{sin^2\theta}}sin\theta cos\theta d\theta$

i recall that $cos^2\theta=1-sin^2\theta$

i tend to be confuse from here onward, pls help!

2. ## Re: trig-substitution!

you'll get cos^2thetha when you'll put 1-sin^2theta=cos^2theta. then you can expand cos^2theta as (cos2theta+1)/2...then integrate cos2theta/2 and 1/2 separately...

3. ## Re: trig-substitution!

$\text{You know that } \int \sqrt{\frac{1-z}{z}}dz = 2\int\sqrt{\frac{1-\sin^{2}(\theta)}{\sin^{2}(\theta)}}\sin(\theta) \cos(\theta)\,\, d\theta$

$\text{ by letting } z = \sin^{2}{(\theta)} \text{ and so } dz = 2\sin{(\theta)}\cos{(\theta)}\,\,d\theta$

Now:

\begin{align*}2\int\sqrt{\frac{1-\sin^{2}(\theta)}{\sin^{2}(\theta)}}\sin(\theta) \cos(\theta)\,\, d\theta =& 2 \int \frac{\sqrt{(\cos^{2}{(\theta)})}}{\sqrt{(\sin^{2} {(\theta)})}} \sin(\theta) \cos(\theta)\,\, d\theta..........[\text{ because } 1 - \sin^{2}(\theta) = \cos^{2}(\theta)] \\ =& 2\int\frac{\cos(\theta)}{\sin(\theta)}\sin(\theta) \cos(\theta)\,\, d\theta \\ =& 2\int\cos^{2}(\theta)\,\, d\theta .....[\text{by using simple algebra}] \\ =& 2\int\frac{\cos(2\theta) + 1}{2}\,\, d\theta ......[\text{because }\cos(2\theta) = 2 \cos^{2}(\theta) - 1] \\ =& 2\left( \int \frac{\cos(2\theta)}{2}d\theta + \int \frac{1}{2}\,\,d\theta\right) \\ =& 2\left(\frac{\sin(2\theta)}{4} + \frac{\theta}{2}\right) + C \\ =& \frac{ \sin(2\theta)}{2} + \theta + C \\ =& \frac{2\sin(\theta)\cos(\theta)}{2} + \theta + C ......[\text{because } \sin(2\theta) = 2\sin(\theta)\cos(\theta)] \\ =& \sin(\theta) \cos(\theta) + \theta + C \end{align*}

By plugging into $\sin(\theta) = \sqrt{z}$, $\cos(\theta) = \sqrt{1 - z}$ and $\theta = \sin^{-1}(\sqrt{z})$ we get:

$\int k\sqrt{\frac{1-z}{z}}dz = \sqrt{z} \sqrt{1 - z} + \sin^{-1}(\sqrt{z}) + C$

And that's it. That's the answer. If you differentiate the new found answer with CAS(like maple) you'll get what you started with which is the given integral in the question. Hope this helps.